A study on the factors affecting use of the Library for the Blind Division by the blind and visually impaired - Bernardo, Julie Ann I.; Aguirre, Vyva Victoria M. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This research sought to determine a user profile of the blind and the visually impaired who visit the Library for the Blind Division and to determine the factors that affect the library usage of the blind and the visually impaired in relation to the library's collection and services. The factors affecting the use of the library are: the need for information, awareness of the collection and services, accessibility and availability of information resources and services, and the problems encountered in the use of library collection and services.
The research method used for this study is the interview. Out of the 21 blind and visually impaired users who were interviewed via mobile/home phones and home visits, only 16 were available for interview. That is because some of them have already changed their contact numbers while others were not anymore residing in the addresses they wrote in the contact list provided by the LBD Librarian. Data gathered from these interviews were tabulated and analyzed using the Statistical Package for the Social Sciences (SPSS), using frequency and percentage distribution.
This study found out that majority of the respondents gave importance to the use of the Library for the Blind Division. Almost half of the respondent went to the library only occasionally. This may be attributed to the distance of the LBD from their homes or work places or lack of time because they are working. It may also be due to the dated collection that they found unnecessary and not useful to them. Other reasons were inadequacy of collection and difficulty in going to the library by themselves. Many of the respondents' reasons in going to the LBD were: to read for pleasure, to borrow and return library materials and to use the computer services.
Most of the users are satisfied with the overall collection and services of the library. One hundred percent of the respondents asked help from the librarian/staff. This shows the value of librarians to these types of library users. Likewise, the librarian and the library staff were assessed by the respondents as very helpful and very effective.
The need for information, accessibility and availability of the information resources and services, awareness of the collection and services, and the problems encountered in the use of library collection and services are the factors that affect the library usage of the blind and visually impaired. Some recommendations for improvement of the library's resources, facilities and services are offered in this paper based on the comments and suggestions of the respondents and the researcher's observations.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries and the blind -- Philippines -- Manila; Libraries and people with visual disabilities -- Philippines -- Manila; National libraries -- Philippines -- Use studies